Predatory journals / Plenilske revije - Pahor, Dušica (Acta Medico-Biotechnica, 2021)
The name “predatory open access” was first used by Jeffrey Beall, researcher and librarian at the University of Colorado at Denver, to describe journals for profits and not for the promotion of scientific data. In 2010, he published the first list of predatory publishers. Beall's list includes potential, possible, or probable predatory scholarly open-access publishers. Predatory practice includes not only journals, but also monographs, conferences and conference proceedings (1).